The Role of Education and Training in Preparing Sustainable Business Models for Small and Medium Enterprises: Current Experiences and Empirical Research - Aliona Lisii; Anna Volosiuc (Ovidius University Annals: Economic Sciences Series, 2025)
This study examines the critical role of education and training in developing sustainable business models for small and medium enterprises (SMEs). Using Moldova as a case study, the research highlights the importance of structured educational programs and training practices in addressing strategic and operational challenges faced by SMEs in their transition to sustainability. Key findings reveal that targeted educational initiatives not only enhance SMEs' ability to implement sustainable practices but also strengthen their resilience in competitive markets. The paper underscores the integration of theoretical frameworks with practical training methodologies, emphasizing their contribution to achieving long-term environmental, social, and economic goals. By analyzing empirical data and current experiences, the study provides actionable recommendations for policymakers, educators, and entrepreneurs aimed at fostering sustainability in the SME sector.